2017
DOI: 10.1371/journal.pone.0183458
|View full text |Cite
|
Sign up to set email alerts
|

MammaPrint versus EndoPredict: Poor correlation in disease recurrence risk classification of hormone receptor positive breast cancer

Abstract: IntroductionCorrect risk assessment of disease recurrence in patients with early breast cancer is critically important to detect patients who may be spared adjuvant chemotherapy. In clinical practice this is increasingly done based on the results of gene expression assays. In the present study we compared the concordance of the 70-gene signature MammaPrint (MP) with the 12 gene assay EndoPredict (EP).MethodsRepresentative tissue of 48 primary tumours was analysed with the MP during routine diagnostic purposes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 47 publications
3
12
0
1
Order By: Relevance
“…An emerging number of papers have addressed the impact of multigene tests on adjuvant chemotherapy decisions by physicians. A recently published paper comparing MammaPrint and EndoPredict risk stratification showed a poor correlation between the two tests and noted that following EndoPredict results in the study, a change in therapy decisions in favor of adding chemotherapy to hormone therapy would have occurred in 38% of the patients . Another recent study by the SAKK 26/10 analyzed the decision impact of Oncotype DX testing and reported a change in therapy decision against chemotherapy and in favor of hormone therapy alone in 44% of the patients .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An emerging number of papers have addressed the impact of multigene tests on adjuvant chemotherapy decisions by physicians. A recently published paper comparing MammaPrint and EndoPredict risk stratification showed a poor correlation between the two tests and noted that following EndoPredict results in the study, a change in therapy decisions in favor of adding chemotherapy to hormone therapy would have occurred in 38% of the patients . Another recent study by the SAKK 26/10 analyzed the decision impact of Oncotype DX testing and reported a change in therapy decision against chemotherapy and in favor of hormone therapy alone in 44% of the patients .…”
Section: Discussionmentioning
confidence: 99%
“…A recently published paper comparing MammaPrint and EndoPredict risk stratification showed a poor correlation between the two tests and noted that following EndoPredict results in the study, a change in therapy decisions in favor of adding chemotherapy to hormone therapy would have occurred in 38% of the patients. 56 Another recent study by the SAKK 26/10 analyzed the decision impact of Oncotype DX testing and reported a change in therapy decision against chemotherapy and in favor of hormone therapy alone in 44% of the patients. 57 A similar recent UK study reported a change against chemotherapy in favor of endocrine therapy alone in 69.2% of patients after the Oncotype DX results were discussed in an interdisciplinary meeting.…”
Section: Discussionmentioning
confidence: 99%
“… 30 This is because these gene-expression biomarkers share common molecular pathways centred on cell proliferation and cell cycle regulation, which are the key components of the well-established pathological parameters. 30 Moreover, MammaPrint and EndoPredic have been found to give different treatment recommendations for a portion of patients and cannot be used interchangeably, 31 while Oncotype DX and MammaPrint offer different prognostic information to the same patients. 32 Another issue with multigene tests is that some patients will still have an “intermediate” risk score, leading to an inconclusive prognosis, 26 though chemotherapy may be surely spared in patients at intermediate recurrence scores as shown in the recent prospective TAILORx trail.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent results raise concerns regarding their predictive clinical value. 58 , 59 The major problem is the selection of biomarkers due to the small number of samples compared with a very high number of features. The Cancer Genome Atlas 60 and the International Cancer Genome Consortium data portal 61 are, by far, the most comprehensive repositories for clinical cancer omics data worldwide.…”
Section: Basic Science and Data For Network And Systems Medicinementioning
confidence: 99%